Mental Health, Culture and Resilience—Approaching the COVID-19 Pandemic From a South African Perspective - Mashaphu, Sibongile; Talatala, Mvuyiso; Seape, Sebolelo; Eriksson, Lennart; Chiliza, Bonginkosi (Frontiers in Psychiatry, 2021)
It is understandable that the challenges of living through a severe contagious outbreak, like the coronavirus disease 2019 (COVID-19), cannot be tolerated for long and that some individuals may require emotional, psychological, and spiritual support in order to strengthen their resilience to navigate this difficult period. As clinicians and researchers in the field of mental health, we need to appreciate the roles that culture, spirituality, and religion play in comforting people who survive such an outbreak and provide possible solutions for public health authorities on how to promote wellness. This appreciation should direct us to seek a deeper understanding of how culture, spirituality, and religion can be used to endure an outbreak of this magnitude and how the interruption of common practices can impact the coping skills of those who are affected. Our understanding of the roles that customs, beliefs, and values of South Africans play in building resilience will help inform and strengthen interventions that are aimed at controlling the spread of COVID-19.